3D printing concrete material containing composite filler and preparation method thereof
By using composite fillers in 3D printed concrete, the multi-scale defects caused by the printing process are solved, the mechanical and permeability of concrete is improved, and better building material performance is achieved.
Patent Information
- Application Number
- CN202411290751.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-07
AI Technical Summary
3D printed concrete materials are difficult to automatically fill due to multi-scale defects caused by printing processes, resulting in poor mechanical anisotropy and impermeability, which cannot meet building requirements.
Using composite filler, by mixing water-absorbing resin, polyacrylamide, cellulose ether and sheet clay evenly, adding aqueous polymer monomer and curing agent to form composite filler with water-sustaining release and multi-scale filling characteristics. Add to concrete to fill internal defects.
Effectively fill the multi-scale defects of 3D printed concrete, improve its mechanical and permeability after hardening, avoid the poor homogeneity caused by conventional highly absorbent resins, and improve the extrusion performance during printing.
Smart Images

Figure CN119263726A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of 3D printing concrete, and in particular relates to a 3D printing concrete material containing a composite filler and a preparation method thereof. Background Art
[0002] 3D printing concrete technology is an important part of the field of intelligent construction. It produces preset buildings by stacking concrete materials layer by layer along a preset path. It has the unique advantages of digital modeling, efficient production and moldless construction.
[0003] Due to the special manufacturing process, the defects inside 3D printed concrete after printing cannot be eliminated through the vibration process. The defects come from the air left inside the multi-layer structure during the printing process, the friction between the coarse aggregate and the cement paste, and the evaporation and loss of the water film layer on the outer surface after the strip is left to stand. Therefore, it has the characteristics of multi-scale pore size. The rheological properties of 3D printed concrete materials in the printing stage and the loss of water in the hardening stage control the formation of multi-scale defects in 3D printed concrete materials. The existence of multi-scale defects will cause the 3D printed concrete materials to have mechanical anisotropy and poor impermeability, making it difficult to meet the requirements of 3D printed buildings.
[0004] Among the technical means of reducing multi-scale defects in 3D printed concrete by adding external components, the method of adding super absorbent resin is a feasible method. It utilizes the fact that after the super absorbent resin is saturated with water and added to concrete, it can release water due to gradient difference during the hardening process of concrete, thereby improving the concrete microstructure to promote the closure of concrete micro defects. However, since the swelling and water release process of conventional super absorbent resin in concrete after absorbing water is extremely fast, it is easy to cause new problems such as increased average diameter of defects and poor structural homogeneity. In addition, this method is not effective for large pore defects (>1mm) caused by the presence of coarse aggregate. 3 ) cannot produce any filling effect, and will also form spherical cavities in the water-absorbing resin particles in situ, which is not conducive to the mechanical and impermeability properties of concrete after hardening. In order to realize the automatic filling of multi-scale defects in 3D printed concrete, new improvements to 3D printed concrete materials are needed to meet people's needs.
[0005] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0006] The purpose of the present invention is to provide a 3D printing concrete material containing a composite filler and a preparation method thereof, so as to help solve or improve the problems of multi-scale defects and difficulty in automatic filling in 3D printing concrete in the prior art.
[0007] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a 3D printing concrete material containing a composite filler, wherein the 3D printing concrete material containing a composite filler comprises the following components: a cementitious material, a fine aggregate, a coarse aggregate, a water reducing agent, a composite filler and water; the composite filler is prepared by a method comprising the following steps: (1) mixing a water-absorbent resin, polyacrylamide and cellulose ether to form a composite filler precursor; (2) placing the composite filler precursor in water, adding flaky clay and stirring the mixture thoroughly, and drying the mixture into powder to obtain a composite filler intermediate; (3) adding the composite filler intermediate to an aqueous polymer monomer and a curing agent and stirring the mixture again to obtain the composite filler.
[0008] Preferably, in step (1), the water-absorbent resin is anionic polyacrylic acid sodium salt, and the free water absorption rate of the water-absorbent resin is 500-800 g / g; the polyacrylamide is cationic polyacrylamide; the cellulose ether is hydroxypropyl methyl cellulose ether, and the surface charge is neutral; the mass ratio of the polyacrylic acid sodium salt, the cationic polyacrylamide and the hydroxypropyl methyl cellulose ether is (7-9):(0.5-1.5):(0.5-1.5).
[0009] Preferably, the relative molecular mass of the sodium polyacrylate is 12 million to 30 million, and the particle size is 50 to 200 μm; the relative molecular mass of the polyacrylamide is 8 million to 12 million; and the hydroxypropyl methylcellulose ether is hydroxypropyl methylcellulose ether with a viscosity unit of 200,000.
[0010] Preferably, in step (2), the clay is montmorillonite, and the particle size of montmorillonite is 0.075-0.15 mm; the mass ratio of the composite filler precursor to water is 1:(45-55), and the mass ratio of clay to the composite filler precursor is 1:(9-11); and the stirring time after adding the flaky clay is 25-35 min.
[0011] Preferably, in step (3), the water-based polymer monomer is bisphenol A epoxy resin, and the equivalent of bisphenol A epoxy resin is 185-195 g / eq; the curing agent is triethylenetetramine, and the equivalent of triethylenetetramine is 20-30 g / eq; the mass ratio of the composite filler intermediate, the water-based polymer monomer and the curing agent is (1-3):10:10.
[0012] Preferably, the 3D printing concrete material containing a composite filler comprises the following components, in parts by weight: 100 parts of cementitious material, 55-100 parts of fine aggregate, 85-145 parts of coarse aggregate, 0.1-0.5 parts of water reducer, 0.5-4 parts of composite filler and 30-40 parts of water.
[0013] Preferably, the cementitious material is ordinary Portland cement and / or sulphoaluminate cement; the particle size of the fine aggregate is 0.15-4.75 mm, and the fine aggregate is at least the same among natural river sand, desalinated sea sand and quartz sand; the particle size of the coarse aggregate is divided into two gradients of 4.75-10 mm and 10-20 mm according to the grading, and the mass ratio is (4-6):(4-6); the coarse aggregate is at least one of gravel aggregate, crushed stone aggregate, slag aggregate and sea gravel aggregate; the water reducer is a polycarboxylic acid-based water reducer.
[0014] The present invention also provides a method for preparing the 3D printing concrete material containing a composite filler as described above, which adopts the following technical scheme: The method for preparing the 3D printing concrete material containing a composite filler as described above comprises the following steps: (i) mixing the cementitious material, fine aggregate and coarse aggregate evenly to obtain a solid mixture for standby use; (ii) dissolving the water reducer and water and stirring evenly to obtain a liquid mixture for standby use; (iii) sequentially adding the liquid mixture and the composite filler to the solid mixture and stirring evenly to obtain the 3D printing concrete material containing the composite filler.
[0015] The present invention also provides an application of the 3D printing concrete material containing the composite filler as described above, which adopts the following technical solution: application of the 3D printing concrete material containing the composite filler as described above in the field of construction engineering.
[0016] Preferably, the 3D printing concrete material containing the composite filler is used to make at least one of 3D printing special-shaped components, 3D printing buildings and 3D printing decorative materials.
[0017] Beneficial effects:
[0018] The composite filler used in the 3D printing concrete material containing the composite filler of the present invention has the characteristics of slow water release and multi-scale filling. It can not only automatically fill the defects inside the 3D printing concrete caused by the printing process during the printing and molding stage, but also improve the density of the internal microstructure of the 3D printing concrete after hardening, thereby improving the mechanical and anti-seepage properties of the 3D printing concrete after hardening.
[0019] The composite filler used in the present invention can significantly fill the micropores generated by water evaporation in 3D printed concrete by adjusting the water release rate of the water-absorbent resin, while avoiding the problem of poor internal homogeneity of 3D printed concrete caused by conventional super absorbent resins. The reasons are: (1) After the water-absorbent resin inside the composite filler absorbs water, the polyacrylamide and cellulose ether used have been adsorbed to the surface of the water-absorbent resin to form a film. In addition, the presence of layered and flaky clay around the water-absorbent resin slows down the rate of water absorption and release inside the water-absorbent resin, avoiding the problem of poor internal homogeneity of 3D printed concrete caused by the conventional super absorbent resin in the prior art absorbing the surrounding free water too quickly (clay helps to improve swelling and plasticity (surface hydroxyl groups), so that the water-absorbent resin absorbs water slowly and avoids dryness and hardness, and then (2) After the 3D printed concrete with the composite filler is printed and left to stand, the water released from the water-absorbing resin due to the concentration gradient difference must first pass through the surrounding solidified water-based polymer layer before it can contact the cement gel in the 3D printed concrete, and then be transmitted to the channel where the evaporated water is retained, thereby promoting the hydration process of the cement gel around the channel to fill the evaporation pores there. In this process, the problem of water being retained in situ and low transmission efficiency due to the water-absorbing resin releasing water too quickly is avoided.
[0020] The composite filler used in the present invention can improve the internal defects of 3D printed concrete other than evaporation defects by adding water-based polymers. The reason is that the bisphenol A epoxy resin used in the present invention undergoes a cross-linking reaction after mixing with triethylenetetramine to form a cross-linked three-dimensional grid network, which has the swelling properties of organic polymers in the new state and can spontaneously flow to the interior of the concrete>1mm after mixing with the 3D printed concrete. 3 The non-evaporation defect position can be filled after the solidification is completed.
[0021] The composite filler used in the present invention can effectively improve the extrudability of 3D printed concrete, and the reasons are as follows: (1) the main mobile phase of 3D printed concrete is cement paste, and cement paste is a plastic fluid. After the water-based epoxy resin of the dilatant plastic fluid is added, the network structure formed in the cement paste will be partially penetrated and replaced by the water-based epoxy resin, reducing the internal friction between various particles in the concrete, thereby reducing the initial shear strength of the composite paste, which is beneficial to improving the smoothness and continuity of the 3D printed concrete when it is extruded from the printer under shear during printing; (2) the surface of the water-absorbent resin in the composite filler adsorbs hydroxypropyl methylcellulose ether, which can be used as a non-ionic surfactant with hydroxyl groups on the surface, has excellent water solubility, and can form a uniformly distributed colloid in the 3D printed concrete with the dispersion of the water-absorbent resin, which can improve the stability of the printed slurry and avoid the occurrence of slurry segregation and water bleeding, which is beneficial to improving the stability and uniformity of the 3D printed concrete when it is extruded from the printer under shear during printing.
[0022] The 3D printed concrete material containing a composite filler proposed in the present invention has better mechanical properties and impermeability after hardening. The reason is that the special stacking production process of 3D printed concrete makes its moisture easily evaporate and dissipate to form micropores. In addition, the presence of coarse aggregate makes the friction between the internal particles of the 3D printed concrete higher and more likely to produce large defects. Therefore, the internal defects of the 3D printed concrete have amorphous and cross-scale characteristics, which are the main reasons that the macroscopic mechanical strength of the 3D printed concrete is lower than that of the cast concrete with the same mix ratio, there are mechanical anisotropy characteristics, external water infiltration is rapid and the impermeability is poor; after the composite filler is added, various defects in the above-mentioned 3D printed concrete can be effectively filled, so that the 3D printed concrete material has better mechanical properties and impermeability after hardening. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0024] Figure 1 Test water head determination for 3D X-ray microscope.
[0025] Figure 2 For 3D X-ray microscope testing water penetration height assessment. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0027] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0028] In view of the problems that the current 3D printing concrete has multi-scale defects and is difficult to automatically fill, the present invention provides a 3D printing concrete material containing a composite filler.
[0029] The 3D printing concrete material containing a composite filler according to an embodiment of the present invention comprises the following components: a cementitious material, a fine aggregate, a coarse aggregate, a water reducing agent, a composite filler and water; wherein the composite filler is prepared by a method comprising the following steps: (1) a water-absorbing resin, a polyacrylamide and a cellulose ether are stirred evenly to form a composite filler precursor; (2) the composite filler precursor is placed in water, flaky clay is added and stirred thoroughly, and a composite filler intermediate is obtained after drying into powder; and (3) the composite filler intermediate is added to an aqueous polymer monomer and a curing agent and stirred evenly again to obtain the composite filler. The introduction of polyacrylamide (used to be adsorbed on the surface of the water-absorbent resin to control the free water content; and also helps to increase the viscosity of the concrete) and cellulose ether (which will affect the dispersibility of the composite filler, help to improve the stability of the composite filler, reduce the internal stress caused by the rapid expansion of the water-absorbent resin, improve the internal curing effect, and increase the viscosity of the concrete) in step (1) helps to slow down the water release rate of the water-absorbent resin; in step (2), the introduction of clay helps to form a layer of dispersed micro-layered structure around the water-absorbent resin, which helps to slow down the water release rate of the water-absorbent resin; in step (3), by introducing water-based polymer monomers and curing agents into the composite filler intermediate, the composite filler has epoxy resin inside, which can not only effectively improve the flow properties and mechanical elastic-plastic properties of 3D printed concrete in the printed state to improve the constructability of 3D printed concrete, but also fill the defects inside the 3D printed concrete during printing due to the spontaneous expansion properties, thereby compensating for the problem that the water-absorbent resin cannot fill the larger defects inside the concrete.
[0030] The composite filler in the 3D printing concrete material containing the composite filler of the present invention has the characteristics of slow release of water and multi-scale filling. It can not only automatically fill the defects inside the 3D printing concrete caused by the printing process during the printing and molding stage, but also improve the density of the internal microstructure of the 3D printing concrete after hardening, thereby improving the mechanical and anti-permeability properties of the 3D printing concrete after hardening.
[0031] In a preferred embodiment of the 3D printing concrete material containing a composite filler of the present invention, in step (1), the water-absorbent resin is an anionic sodium polyacrylate, and the free water absorption rate of the water-absorbent resin is 500-800 g / g (for example, 500 g / g, 600 g / g, 700 g / g or 800 g / g; the free water absorption rate FSC measures how many times the weight of water a resin can absorb when it expands freely in deionized water; a water-absorbent resin with a free water absorption rate of 500-800 g / g is a highly absorbent resin); cellulose The ether is hydroxypropyl methylcellulose ether, and the surface charge is neutral (i.e., the surface has no charge); the polyacrylamide is cationic polyacrylamide; the mass ratio of polyacrylic acid sodium salt, cationic polyacrylamide and hydroxypropyl methylcellulose ether is (7-9):(0.5-1.5):(0.5-1.5) (e.g., 7:0.5:0.5, 7:1:1, 7:1.5:1.5, 8:0.5:0.5, 8:1:1, 8:1.5:1.5, 9:0.5:0.5, 9:1:1 or 9:1.5:1.5). In step (1), the stirring and mixing method can be to use a forced stirrer, an electric stirrer, a vibrator or other equipment to exert a strong mechanical action on the mixture to disperse the water-absorbing resin, polyacrylamide and cellulose ether, and the stirring time can be 4-6 minutes (e.g., 4 minutes, 5 minutes or 6 minutes; it is sufficient to achieve uniform mixing of the raw materials) to form a uniform composite filler precursor. If the dosage of sodium polyacrylate is too large, the water absorption of the composite filler will increase, which will excessively absorb the free water stock in the concrete, prolong the setting time of the concrete, and affect the early strength development; if the dosage of sodium polyacrylate is too small, the water absorption will decrease, and the water absorption of the composite filler will weaken. In addition, the internal curing (self-healing) effect of the concrete will weaken. If the dosage of cationic polyacrylamide is too large, the water absorption rate of sodium polyacrylate in the composite filler is too low (the surface of sodium polyacrylate is over-adsorbed and difficult to contact with water), and the free water content cannot be effectively controlled, which may increase the viscosity of the concrete; if the dosage of cationic polyacrylamide is too low, sodium polyacrylate absorbs water too quickly, affecting the normal 3D printing process and reducing the anti-permeability performance of the concrete. If the dosage of hydroxypropyl methylcellulose ether is too large, the water absorption / release rate of sodium polyacrylate in the composite filler will slow down (the water film layer on the surface of sodium polyacrylate is thicker and expands slowly), the internal curing effect will deteriorate, and the dispersion of the composite filler will be difficult, while the viscosity of the concrete will also be increased; if the dosage of hydroxypropyl methylcellulose ether is too low, the stability of the composite filler will be weakened, the composite filler itself will be easy to dissociate, the expansion of sodium polyacrylate will be accelerated, internal stress will be easily generated, and the rate at which sodium polyacrylate reserves water will be accelerated, which is not conducive to long-term internal curing.
[0032] In a preferred embodiment of the 3D printing concrete material containing a composite filler of the present invention, the relative molecular mass of sodium polyacrylate is 12 million to 30 million (for example, 12 million, 16 million, 20 million, 25 million or 30 million), and the particle size is 50 to 200 μm (50 μm, 100 μm, 150 μm or 200 μm); the relative molecular mass of polyacrylamide is 8 million to 12 million (8 million, 9 million, 10 million, 11 million or 12 million); and the hydroxypropyl methylcellulose ether is hydroxypropyl methylcellulose ether with a viscosity unit of 200,000. Among them, the anionic polyacrylic acid sodium salt particles selected in the present invention have the characteristics of rapid water absorption and water release; the polyacrylamide selected in the present invention can form a good adsorption effect on the water-absorbent resin, slowing down the water release rate of the highly absorbent resin; the cellulose ether selected in the present invention has no electrical surface, is easy to disperse in water, can produce a good adsorption and film-forming effect on the water-absorbent resin, and slows down the water release rate of the water-absorbent resin.
[0033] In a preferred embodiment of the 3D printing concrete material containing a composite filler of the present invention, in step (2), the clay is montmorillonite, and the particle size of the montmorillonite is 0.075-0.15 mm (for example, 0.075 mm, 0.09 mm, 0.11 mm, 0.13 mm or 0.15 mm); the mass ratio of the composite filler precursor to water is 1:(45-55) (for example, 1:45, 1:48, 1:50, 1:53 or 1:55), and the mass ratio of montmorillonite to the composite filler precursor is 1:(9-11) (for example, 1:9, 1:10 or 1:11); the stirring time after adding the flaky clay is 25-35 min (for example, 25 min, 28 min, 30 min, 32 min or 35 min). The present invention uses montmorillonite with a particle size of 0.075 to 0.15 mm, which helps to form a dispersed microscopic layered structure around the water-absorbent resin, thereby slowing down the water release rate of the water-absorbent resin. In step (2), the stirring method can be stirring with a magnetic stirrer to allow the polyacrylamide, cellulose ether, and flaky clay to be well adsorbed to the surface of the water-absorbent resin; if the stirring time is too long, separation will occur; if the stirring time is too short, the montmorillonite will not be sufficiently attached to the surface of the composite filler precursor. When drying, try to increase the temperature slowly to avoid sudden changes in the material structure; drying can completely dehydrate the composite filler precursor and montmorillonite, and the drying temperature should be less than about 200°C to avoid thermal decomposition of the composite filler intermediate during the drying process; for example, the drying temperature can be 130-150°C, or 105°C (drying time is 8h), etc., and the composite filler intermediate can be fully dried under the premise that the drying temperature does not cause decomposition or structural mutation of the composite filler intermediate and / or the composite filler precursor; through drying treatment, the solute in the solution can be completely converted into a composite filler intermediate in a dry powder state, which is convenient for further use of the composite filler intermediate to prepare a composite filler. If the drying is insufficient, it will have an adverse effect on the water absorption-release effect of the prepared composite filler, and thus affect the improvement effect of the composite filler on the performance of 3D printed concrete.
[0034] In a preferred embodiment of the 3D printing concrete material containing a composite filler of the present invention, in step (3), the aqueous polymer monomer is a bisphenol A epoxy resin, and the equivalent of the bisphenol A epoxy resin is 185-195 g / eq (for example, 185 g / eq, 190 g / eq or 195 g / eq); the curing agent is triethylenetetramine, and the equivalent of triethylenetetramine is 20-30 g / eq (for example, 20 g / eq, 22 g / eq, 24 g / eq , 26g / eq, 28g / eq or 30g / eq); the mass ratio of the composite filler intermediate, the water-based polymer monomer and the curing agent is (1-3): 10:10 (for example, 1:10:10, 1.5:10:10, 2:10:10, 2.5:10:10 or 3:10:10); wherein, the present invention adopts the above-mentioned water-based polymer monomer and curing agent, and the two can form a stable network structure after polymerization, and have the property of swelling. The stirring in step (3) can achieve uniform mixing of the raw materials. During stirring, a forced mixer, an electric stirrer, a vibrator or other equipment can be used as needed to produce a strong mechanical action on the mixture to make each component fully mixed. The stirring time can be 5 minutes to form a uniform composite filler.
[0035] In a preferred embodiment of the 3D printing concrete material containing a composite filler of the present invention, the 3D printing concrete material containing a composite filler of the embodiment of the present invention includes the following components, in parts by weight: 100 parts of a cementitious material, 55 to 100 parts of a fine aggregate (e.g., 55 parts, 60 parts, 70 parts, 80 parts, 90 parts or 100 parts), 85 to 145 parts of a coarse aggregate (e.g., 85 parts, 95 parts, 105 parts, 115 parts, 125 parts, 135 parts or 145 parts), 0.1 to 0.5 parts of a water reducer (e.g., 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts), 0.5 to 4 parts of a composite filler (e.g., 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts or 5 parts), and 30 to 40 parts of water (e.g., 30 parts, 32 parts, 34 parts, 36 parts, 38 parts or 40 parts).
[0036] In a preferred embodiment of the 3D printing concrete material containing a composite filler of the present invention, the cementitious material is ordinary Portland cement and / or sulphoaluminate cement; the particle size of the fine aggregate is 0.15-4.75 mm, and the fine aggregate is at least the same as natural river sand, desalinated sea sand and quartz sand; the coarse aggregate particle size is divided into two gradients of 4.75-10 mm and 10-20 mm according to the grading, and the mass ratio is (4-6):(4-6) (for example, 2:3, 1:1 or 3:2); the coarse aggregate is at least one of gravel aggregate, crushed stone aggregate, slag aggregate and sea gravel aggregate; the water reducer is a polycarboxylic acid water reducer.
[0037] The present invention also proposes a method for preparing the 3D printing concrete material containing a composite filler of the present invention as described above. The method for preparing the 3D printing concrete material containing a composite filler in an embodiment of the present invention comprises the following steps: (i) mixing a cementitious material, a fine aggregate, and a coarse aggregate evenly to obtain a solid mixture for standby use; (ii) dissolving a water reducer and water and stirring evenly to obtain a liquid mixture for standby use; (iii) sequentially adding the liquid mixture and the composite filler to the solid mixture (applying the composite filler to the preparation of 3D printing concrete before the water-based polymer monomer is cured), stirring evenly, and obtaining a 3D printing concrete material containing a composite filler.
[0038] The present invention also proposes the application of the 3D printing concrete material containing the composite filler as described above, and the application of the 3D printing concrete material containing the composite filler as described above in the field of construction engineering.
[0039] In a preferred embodiment of the application of the 3D printing concrete material containing a composite filler of the present invention, the 3D printing concrete material containing a composite filler is used to make at least one of 3D printed large-scale special-shaped components, 3D printed buildings, and 3D printed decorative materials.
[0040] The 3D printing concrete material containing a composite filler and a preparation method thereof of the present invention are described in detail below through specific embodiments.
[0041] The raw materials used in the following examples are all commercially available, and the main raw materials used are purchased from Qingdao Kremer New Building Materials Technology Co., Ltd.
[0042] Example 1
[0043] The 3D printing concrete material containing a composite filler in this embodiment includes, by weight: 100 parts of cementitious material, 75 parts of fine aggregate, 120 parts of coarse aggregate, 0.3 parts of water reducing agent, 2 parts of composite filler and 35 parts of water.
[0044] Among them, the cementitious material is ordinary Portland cement (PO 42.5 ordinary Portland cement), the fine aggregate is natural river sand with a particle size of 0.15-4.75 mm, the coarse aggregate is gravel aggregate with two gradients of 4.75-10 mm and 10-20 mm (mass ratio of 3:2), and the water reducer is a polycarboxylic acid water reducer with a solid content of 33% and a water reduction rate of 35%.
[0045] The composite filler is prepared by a method comprising the following steps:
[0046] (1) mixing a water-absorbent resin (the water-absorbent resin is an anionic polyacrylic acid sodium salt with a relative molecular mass of 12 million and a particle size of 50 μm), polyacrylamide (the polyacrylamide is a cationic polyacrylamide with a relative molecular mass of 8 million), and cellulose ether (the cellulose ether is hydroxypropyl methylcellulose ether with a viscosity unit of 200,000) in a mass ratio of 8:1:1, and stirring for 5 minutes using an electric stirrer to obtain a powdery composite filler precursor (highly water-absorbent resin particles covered with polyacrylamide and cellulose ether);
[0047] (2) placing the composite filler precursor in water at a mass ratio of 1:50, mixing the flaky clay (the flaky clay is montmorillonite with a particle size of 0.075 to 0.15 mm) with the composite filler precursor obtained in step (1) at a mass ratio of 1:10, and stirring them thoroughly for 30 minutes using a magnetic stirrer, and then drying the mixed solution in a dryer at 105° C. for 8 hours to obtain a powdered composite filler intermediate;
[0048] (3) The composite filler intermediate, the water-based polymer monomer (the water-based polymer monomer is a bisphenol A epoxy resin with an equivalent weight of 190 g / eq), and the curing agent (the curing agent is triethylenetetramine with an equivalent weight of 24 g / eq) are mixed in a mass ratio of 1:10:10, and then stirred for 3 minutes using an electric stirrer to obtain a composite filler.
[0049] The method for preparing the 3D printing concrete material containing the composite filler of this embodiment comprises the following steps:
[0050] (i) mixing the cementitious material, fine aggregate and coarse aggregate uniformly to obtain a solid mixture for later use;
[0051] (ii) The water reducing agent is mixed with water to dissolve and stirred with an electric stirrer for 3 minutes to obtain a liquid mixture for later use.
[0052] (iii) The liquid mixture and the composite filler are sequentially added to the solid mixture, and stirred for 5 minutes using a forced mixer to obtain the 3D printing concrete material containing the composite filler of this embodiment.
[0053] Example 2
[0054] The 3D printing concrete material containing a composite filler in this embodiment includes, by weight: 100 parts of cementitious material, 55 parts of fine aggregate, 85 parts of coarse aggregate, 0.1 parts of water reducing agent, 2 parts of composite filler and 35 parts of water.
[0055] The difference between the composite filler and the composite filler of Example 1 is that the relative molecular mass of the water-absorbent resin is 30 million and the particle size is 200 μm; the relative molecular mass of the polyacrylamide is 12 million; and the rest is consistent with Example 1.
[0056] The preparation method of the 3D printing concrete material containing the composite filler in this embodiment, as well as the selection of the cementitious material, fine aggregate, coarse aggregate and water reducing agent are the same as those in Example 1.
[0057] Example 3
[0058] The 3D printing concrete material containing a composite filler in this embodiment includes, by weight: 100 parts of cementitious material, 75 parts of fine aggregate, 120 parts of coarse aggregate, 0.3 parts of water reducing agent, 0.5 parts of composite filler and 40 parts of water.
[0059] The difference between the composite filler and the composite filler of Example 1 is that in step (3), the composite filler intermediate, the aqueous polymer monomer and the curing agent are mixed in a mass ratio of 3:10:10; the rest is the same as Example 1.
[0060] The preparation method of the 3D printing concrete material containing the composite filler in this embodiment, as well as the selection of the cementitious material, fine aggregate, coarse aggregate and water reducing agent are the same as those in Example 1.
[0061] Example 4
[0062] The 3D printing concrete material containing a composite filler in this embodiment includes, by weight: 100 parts of cementitious material, 100 parts of fine aggregate, 145 parts of coarse aggregate, 0.5 parts of water reducing agent, 0.5 parts of composite filler and 35 parts of water.
[0063] The difference between the composite filler and the composite filler of Example 1 is that in step (3), the composite filler intermediate, the aqueous polymer monomer and the curing agent are mixed in a mass ratio of 2:10:10; the rest is the same as Example 1.
[0064] The preparation method of the 3D printing concrete material containing the composite filler in this embodiment, as well as the selection of the cementitious material, fine aggregate, coarse aggregate and water reducing agent are the same as those in Example 1.
[0065] Example 5
[0066] The 3D printing concrete material containing a composite filler in this embodiment includes, by weight: 100 parts of cementitious material, 75 parts of fine aggregate, 120 parts of coarse aggregate, 0.3 parts of water reducing agent, 4 parts of composite filler and 35 parts of water.
[0067] The difference between the composite filler and the composite filler of Example 1 is that in step (3), the composite filler intermediate, the aqueous polymer monomer and the curing agent are mixed in a mass ratio of 3:10:10; the rest is the same as Example 1.
[0068] The preparation method of the 3D printing concrete material containing the composite filler in this embodiment, as well as the selection of the cementitious material, fine aggregate, coarse aggregate and water reducing agent are the same as those in Example 1.
[0069] Example 6
[0070] The 3D printing concrete material containing a composite filler in this embodiment includes, by weight: 100 parts of cementitious material, 55 parts of fine aggregate, 85 parts of coarse aggregate, 0.3 parts of water reducing agent, 4 parts of composite filler and 30 parts of water.
[0071] The composite filler is the same as the composite filler in Example 1.
[0072] The preparation method of the 3D printing concrete material containing the composite filler in this embodiment, as well as the selection of the cementitious material, fine aggregate, coarse aggregate and water reducing agent are the same as those in Example 1.
[0073] Comparative Example 1
[0074] The 3D printing concrete material of this comparative example is different from that of Example 1 only in that, in the process of preparing the composite filler, polyacrylamide and cellulose ether are not added in step (1), and flaky clay is not added in step (2); the rest is consistent with Example 1.
[0075] Comparative Example 2
[0076] The 3D printing concrete material of this comparative example is different from that of Example 1 only in that: in the process of preparing the composite filler, the drying temperature in step (2) is 85° C. and the drying time is 4 h; the mass ratio of the composite filler precursor to water is 1:100; and the rest is consistent with Example 1.
[0077] Comparative Example 3
[0078] The 3D printing concrete material of this comparative example is different from that of Example 1 only in that the components of the 3D printing concrete material do not include a composite filler; the rest are consistent with Example 1.
[0079] Comparative Example 4
[0080] The 3D printing concrete material of this comparative example is different from that of Example 1 only in that the weight portion of the composite filler in the 3D printing concrete material is 6 parts; the rest is consistent with Example 1.
[0081] Comparative Example 5
[0082] The 3D printing concrete material of this comparative example is different from that of Example 1 only in that, in the process of preparing the composite filler, the mass ratio of the composite filler intermediate, the aqueous polymer monomer, and the curing agent in step (3) is 5:10:10; the rest is the same as that of Example 1.
[0083] Comparative Example 6
[0084] The 3D printing concrete material of this comparative example is different from that of Example 1 only in that: in the process of preparing the composite filler, after obtaining the composite filler intermediate, the composite filler intermediate, the water-based polymer monomer, the curing agent (the ratio of the composite filler intermediate, the water-based polymer monomer and the curing agent is the same as that in Example 1, and the total amount of the three is the same as that of the composite filler in Example 1), the solid mixture and the liquid mixture are mixed; the rest are consistent with Example 1.
[0085] Comparative Example 7
[0086] The 3D printing concrete material of this comparative example is different from that of Example 1 only in that step (3) is omitted, and after obtaining the composite filler intermediate, the composite filler intermediate, the solid mixture and the liquid mixture are mixed; the rest is the same as that of Example 1.
[0087] Experimental example
[0088] The 3D printed concrete materials containing composite fillers prepared in the above embodiments and the 3D printed concrete materials of the comparative example were made into test pieces by using 3D printing technology, and the test pieces were post-processed under the same cutting process and curing conditions. Then, various performance indicators of each concrete sample were tested, and the results are shown in Table 1 below.
[0089] Among them, the compressive strength and flexural strength were tested by SUNS2000kN electro-hydraulic servo universal testing machine; the meso-porosity was tested by German YXLON PRECISION SX-ray tomography scanner; the micro-porosity was tested by ZeissXradia 510Versa three-dimensional X-ray microscope;
[0090] The impermeability was tested using an in-situ cesium ion enhanced development technique using a "water seepage height method" (refer to Chinese patent document with publication number CN105136615A: A method for continuously tracking moisture transmission of cement-based materials); specifically: the 3D printed concrete material containing a composite filler prepared in each embodiment and the 3D printed concrete material of the comparative example were cured under standard conditions for 60 days and then tested according to the method of Example 1 described in the specification of Chinese patent document CN105136615A.
[0091] Test results:
[0092] (1) The test results of compressive strength, flexural strength, mesoporosity, microporosity and water permeability are shown in Table 1 below:
[0093] Table 1
[0094]
[0095]
[0096] The test results in Table 1 show that the 3D printing concrete materials containing composite fillers prepared in Examples 1 to 5 have significant advantages of high mechanical strength, low microscopic porosity, and strong resistance to water penetration. Specifically:
[0097] It can be seen from Example 1 and Comparative Example 1 that the compressive strength (60.2MPa) and flexural strength (6.2MPa) of the 3D printed concrete containing the composite filler in Example 1 are significantly higher than those in Comparative Example 1 (49.4MPa and 4.1MPa), which shows that the composition of the composite filler is very important for improving the strength of concrete. At the same time, the porosity and water permeability of Example 1 are lower than those of Comparative Example 1, indicating that the composite filler of claim 1 helps to improve the density and impermeability of concrete.
[0098] It can be seen from Example 1 and Comparative Example 2 that all performance indicators of Comparative Example 2 are lower than those of Example 1, especially strength and porosity. This is because Comparative Example 2 cannot achieve sufficient drying of the composite filler intermediate, which results in a high water content in the prepared composite filler itself. When it is applied to 3D printed concrete, the composite filler's regulating function of water absorption and release of 3D printed concrete is weakened, which in turn has an adverse effect on the improvement of the mechanical properties, microscopic porosity and resistance to water permeability of 3D printed concrete.
[0099] It can be seen from Example 1 and Comparative Example 3 that the strength and impermeability of Comparative Example 3 without adding the composite filler are significantly inferior to those of Example 1, indicating that the composite filler can play an important role in significantly improving the performance of 3D printed concrete in the present invention.
[0100] It can be seen from Example 1 and Comparative Example 4 that if the amount of composite filler used is too much, not only will the performance of 3D printed concrete not be improved, but it will slightly decrease in some aspects.
[0101] It can be seen from Example 1 and Comparative Example 5 that the performance of Comparative Example 5 is slightly lower than that of Example 1, indicating that the mass ratio of the composite filler intermediate, the water-based polymer monomer, and the curing agent has an impact on the final performance; this is because when the usage ratio of the composite filling intermediate is changed, the water absorption-release performance of the composite filler will be affected, and then when it is applied to 3D printed concrete, it will affect its efficiency in regulating water in the 3D printed concrete, and adversely affect the strength, mesoporosity, microporosity and water permeability rate of the 3D printed concrete.
[0102] It can be seen from Example 1 and Comparative Example 6 that in Comparative Example 6, the water-based polymer monomer and the curing agent are directly added to the 3D printed concrete, which will cause the performance of the 3D printed concrete to deteriorate significantly compared to mixing with the composite filler intermediate and then adding the composite filler to the 3D printed concrete; this is because when the water-based polymer monomer and the curing agent are mixed with the composite filler intermediate to obtain the composite filler, it is helpful to form a water-based polymer on the surface of the composite filler intermediate, and then when water enters the water-absorbent resin, it needs to first pass through the water-based polymer before contacting the composite filler intermediate, causing it to slowly swell and then slowly release water (concentration gradient difference), so as to help improve the performance of the 3D printed concrete; if the water-based polymer monomer is directly mixed with the raw materials of the concrete, it is difficult for the water-based polymer to form a water-based polymer on the surface of the composite filler intermediate, and thus it cannot play a role equivalent to that of the composite filler.
[0103] It can be seen from Example 1 and Comparative Example 7 that the water-based polymer monomer and the curing agent in the present invention can significantly improve the performance of 3D printed concrete.
[0104] (2) Figure 1 and Figure 2 This is the test result of the 3D printing concrete material containing the composite filler of Example 6 when immersed in a 5% CsCl aqueous solution for 24 hours; Figure 1 ((a) is the original image, (b) is the image after highlighting the water seepage area; Figure 1 The water seepage area is shown at the top) is a two-dimensional diagram (three-dimensional X-ray microscope test water head determination diagram), which shows from the two-dimensional perspective that the specific water penetration depth can be obtained by using a ruler; Figure 2 It is a three-dimensional graph (three-dimensional X-ray microscope test water penetration height assessment graph), which is the appearance observed from a three-dimensional angle, and the highest point of the liquid surface is taken as the water penetration depth value.
[0105] In summary, the present invention can effectively improve the strength, density and impermeability of 3D printed concrete by adding composite fillers to 3D printed concrete, providing a reliable material basis for practical applications.
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A 3D printing concrete material containing a composite filler, characterized in that: The 3D printing concrete material containing a composite filler comprises the following components: a cementitious material, fine aggregate, coarse aggregate, a water reducing agent, a composite filler and water; The composite filler is prepared by a method comprising the following steps: (1) stirring a water-absorbent resin, polyacrylamide, and cellulose ether to form a composite filler precursor; (2) placing the composite filler precursor in water, adding flaky clay, stirring thoroughly, and drying into powder to obtain a composite filler intermediate; (3) Adding the composite filler intermediate to the aqueous polymer monomer and the curing agent and stirring them evenly again to obtain the composite filler.
2. The 3D printing concrete material containing composite filler according to claim 1, characterized in that: In step (1), the water-absorbent resin is anionic polyacrylic acid sodium salt, and the free water absorption rate of the water-absorbent resin is 500-800 g / g; the polyacrylamide is cationic polyacrylamide; the cellulose ether is hydroxypropyl methylcellulose ether, and the surface charge is neutral; The mass ratio of the sodium polyacrylic acid salt, cationic polyacrylamide and hydroxypropyl methylcellulose ether is (7-9):(0.5-1.5):(0.5-1.5).
3. The 3D printing concrete material containing composite filler according to claim 2, characterized in that: The relative molecular mass of the sodium polyacrylic acid salt is 12 million to 30 million, and the particle size is 50 to 200 μm; The relative molecular mass of the polyacrylamide is 8 million to 12 million; The hydroxypropyl methylcellulose ether is hydroxypropyl methylcellulose ether with a viscosity unit of 200,000.
4. The 3D printing concrete material containing composite filler according to claim 1, characterized in that: In step (2), the clay is montmorillonite, and the particle size of the montmorillonite is 0.075-0.15 mm; The mass ratio of the composite filler precursor to water is 1:(45-55), and the mass ratio of clay to the composite filler precursor is 1:(9-11); The stirring time after adding the flaky clay is 25 to 35 minutes.
5. The 3D printing concrete material containing composite filler according to claim 1, characterized in that: In step (3), the aqueous polymer monomer is bisphenol A epoxy resin, and the equivalent weight of the bisphenol A epoxy resin is 185 to 195 g / eq; The curing agent is triethylenetetramine, and the equivalent of triethylenetetramine is 20-30g / eq; The mass ratio of the composite filler intermediate, the water-based polymer monomer and the curing agent is (1-3):10:
10.
6. The 3D printing concrete material containing a composite filler according to any one of claims 1 to 5, characterized in that: The 3D printing concrete material containing a composite filler includes the following components, measured in parts by weight: 100 parts of cementitious material, 55 to 100 parts of fine aggregate, 85 to 145 parts of coarse aggregate, 0.1 to 0.5 parts of water reducing agent, 0.5 to 4 parts of composite filler and 30 to 40 parts of water.
7. The 3D printing concrete material containing a composite filler according to any one of claims 1 to 5, characterized in that: The cementitious material is ordinary Portland cement and / or sulphoaluminate cement; The particle size of the fine aggregate is 0.15 to 4.75 mm, and the fine aggregate is at least one of natural river sand, desalinated sea sand and quartz sand; The coarse aggregate particle size is divided into two gradients of 4.75-10 mm and 10-20 mm according to the grading, and the mass ratio is (4-6): (4-6); the coarse aggregate is at least one of gravel aggregate, crushed stone aggregate, slag aggregate and sea gravel aggregate; The water reducing agent is a polycarboxylic acid water reducing agent.
8. The method for preparing a 3D printing concrete material containing a composite filler according to any one of claims 1 to 7, characterized in that: The steps include: (i) mixing the cementitious material, fine aggregate and coarse aggregate uniformly to obtain a solid mixture for standby use; (ii) dissolving the water reducing agent and water and stirring them uniformly to obtain a liquid mixture for standby use; (iii) adding the liquid mixture and the composite filler to the solid mixture in sequence and stirring evenly to obtain the 3D printing concrete material containing the composite filler.
9. Application of the 3D printing concrete material containing composite fillers as described in any one of claims 1 to 7 in the field of construction engineering.
10. The use according to claim 9, characterized in that The 3D printing concrete material containing the composite filler is used to make at least one of 3D printing special-shaped components, 3D printing buildings and 3D printing decorative materials.
Citation Information
Patent Citations
Method for continuously tracking cement-based material water transfer
CN105136615A